José Bové and the Globalisation Countermovement in France and Beyond: A Polanyian Interpretation - Birchfield, Vicki (Review of International Studies, 2005)
This article illustrates the continuing salience of Karl Polanyi's The Great Transformation (1944) by employing two of its central concepts, fictitious commodities and the double movement to interpret the globalisation countermovement and one of its most important figures, José Bové. I explain the transformation of José Bové from rural sheep farmer to French folk hero and global activist and analyse the extent to which his rhetoric and political actions are congruent with Polanyi's key insights. Arguing against the media characterisation of Bové as protectionist, I show that this misrepresentation conceals the larger ideological threat his movement poses to institutionalised politics and neoliberal hegemony. The political vision underlying Bové's symbolic media tactics and articulated in his book, Le Monde n'est pas une Marchandise, reveals significant manifestations of Polanyi's chief intellectual legacy - an unparalleled critique of economism and market society. An often neglected question in Polanyian scholarship is whether or not it is possible to have a market economy without becoming a market society. A more careful analysis of Polanyi's thought sheds light on this key issue while the empirical analysis of Bové's movement reveals its implications for French society and the broader globalisation countermovement.
Political Science
Keywords: capitalism; commodities; countermovement; economic globalization; economic liberalism; free market economies; globalization; international economics; political movements; social movements